Denesuline materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Hoijer, Harry, 1904-1976 (1950)
Two items relating to the Denesuline language have been identified in the C. F. Voegelin Papers. One is in Subcollection I, Series V. Research Notes, Subseries V-C: Other, and consists of notes in both English and French on the Dene alphabet and syllabary in a folder labeled "Inscribed Stone and Syllabary Material. The other is in Subcollection II, Series II. Research Notes, Subseries II. Na-Dene, and consists of a folder labeled "Athabascan (Chipewyan)." Its contents primarily concern Chipewyan, with briefer mentions of Apachean, Navajo, Hupa, Okanagan, Carrier, Chilcotin, Sekani, Beaver, and Tsuut'ina ("Sarcee"). It also includes correspondence with Harry Hoijer, 1950.